Depression, Anxiety and Sleep Alterations in Caregivers of Persons With Dementia After 1-Year of COVID-19 Pandemic - Bussè, Cinzia; Barnini, Teresa; Zucca, Milena; Rainero, Innocenzo; Mozzetta, Stefano; Zangrossi, Andrea; Cagnin, Annachiara (Frontiers in Psychiatry, 2022)
Background Social isolation due to COVID-19 pandemic has an important psychological impact particularly in persons with dementia and their informal caregivers. Aim To assess frequency and severity of long-term stress-related symptoms in caregivers of patients with dementia 1-year after the beginning of COVID-19 pandemic and to identify predictors of psychological outcomes. Methods Eighty-five caregivers were involved in a longitudinal study with 1-year follow-up during pandemic in Italy. At baseline in April 2020 a telephone interview assessed socio-demographic characteristics of caregivers and self-perception of distress symptoms. After 1 year, between March and April 2021, the same standardized interview was delivered to the caregivers' sample. In addition, scales assessing levels of depression and anxiety (DASS-21), sleep disturbances (PSQI) and coping strategies (COPE-NVI) were administered to the caregivers and to 50 age and sex-matched non-caregivers subjects. Linear regression analysis was performed to investigate the power of baseline variables to predict long-term psychological outcomes. Results After 1 year of pandemic frequency of caregivers' stress-related symptoms increased respect to baseline: depression (60 vs. 5, 9%; p < 0.001), anxiety (45, 9 vs. 29, 4%; p = 0.035), irritability (49, 4 vs. 24, 7%; p < 0.001), and anguish (31, 7 vs. 10, 6%; p < 0.001). Frequency of severe depression was higher in caregivers than in non-caregivers (p = 0.002) although mean levels of depression were comparable in the two groups. Long-term higher depression was predicted by a model built on baseline information (r2 = 0.53, p < 0.001) where being female (t = −3.61, p < 0.001), having lower education (t = −2.15, p = 0.04), presence of feelings of overwhelm (t = 2.29, p = 0.02) and isolation (t = 2.12, p = 0.04) were significant predictors. Female sex was also predictive of anxiety (t = −2.7, p = 0.01) and poor sleep quality (t = −2.17, p = 0.03). Discussion At 1 year follow-up caregivers of patients with dementia reported higher prevalence of all stress-related symptoms respect to the acute phase of lockdown, particularly depression. Long-lasting stressful conditions may cause exhaustion of resilience factors and increased depression. Planning interventions should support caregivers to enable them to continue with their role during pandemic.